2022
DOI: 10.1029/2022gh000620
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Impacts Can Be Differentially Perceived Across Time Scales: A Study Among the Tuareg of the Algerian Sahara

Abstract: As an Indigenous community of Algeria and the broader Sahel, the Tuareg hold unique ecological knowledge, which might contribute to broader models of place‐based climate change impacts. Between January and April 2019, we carried out semi‐structured interviews ( N = 23) and focus group discussions ( N = 3) in five villages of the province of Illizi, Algeria, to document the local Tuareg community's timeline and ecological calendar, both of which are instruments used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…Second, data collected through this protocol will improve our understanding of the impacts of climate change on local livelihoods, from changes in cropping patterns and damages related to extreme events [ 33 ], to disease outbreaks or to the increase in conflicts over dwindling resources [ 34 ]. While responding to climate change demands adjusting to weather and climate changes; identifying risks, making decisions on how to respond, and implementing such decisions are all mediated by socioeconomic and cultural factors [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, data collected through this protocol will improve our understanding of the impacts of climate change on local livelihoods, from changes in cropping patterns and damages related to extreme events [ 33 ], to disease outbreaks or to the increase in conflicts over dwindling resources [ 34 ]. While responding to climate change demands adjusting to weather and climate changes; identifying risks, making decisions on how to respond, and implementing such decisions are all mediated by socioeconomic and cultural factors [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second challenge is to adequately capture the temporal dimension of change, as neglecting it might lead to conflate climate change and weather variability. For example, in a case study derived from this work [ 33 ], researchers found that Tuareg participants reported the impact of rain and temperature irregularities and severe drought events on their pastoral and semi-pastoral livelihoods. Paradoxically, they did not explicitly report decadal trends in the frequency of extreme events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ref. [70] recorded that the floods caused huge damage to the village in the Tuareg oasis (Algerian Sahara), which led to the migration of residents away from the streams. On the other hand, the expansion of urbanization inside the villages of Ziz have developed new tourist and commercial spaces, which create new opportunities for visitors and local populations.…”
Section: Land Cover Analysismentioning
confidence: 99%
“…The Indigenous communities featured in our Special Issue are responding to both long‐term trends and increasing variability in the climate. In “Climate Change Impacts Can Be Differentially Perceived Across Time Scales: A Study Among the Tuareg of the Algerian Sahara,” an international team led by an Algerian scholar (Miara et al., 2022 ) apply a protocol developed by the Local Indicators of Climate Change Impacts initiative to evaluate local knowledge of climate changes in relation to livelihood activities and cultural practices. The authors find that Tuareg participants are more keenly aware of interannual (cyclical) variability, which they attribute to climate change, than they are of longer‐term trends, despite providing evidence of dramatic changes over the past several decades.…”
Section: The Insights That Link the Contributing Articlesmentioning
confidence: 99%